A yeast-like mRNA capping apparatus in Plasmodium falciparum - Ho, C. Kiong (The National Academy of Sciences, 2001)
Analysis of the mRNA capping apparatus of the malaria parasite Plasmodium falciparum illuminates an evolutionary connection to fungi rather than metazoans. We show that P. falciparum encodes separate RNA guanylyltransferase (Pgt1) and RNA triphosphatase (Prt1) enzymes and that the triphosphatase component is a member of the fungal/viral family of metal-dependent phosphohydrolases, which are structurally and mechanistically unrelated to the cysteine-phosphatase-type RNA triphosphatases found in metazoans and plants. These results highlight the potential for discovery of mechanism-based antimalarial drugs designed to specifically block the capping of Plasmodium mRNAs. A simple heuristic scheme of eukaryotic phylogeny is suggested based on the structure and physical linkage of the triphosphatase and guanylyltransferase enzymes that catalyze cap formation.